“Always Look on the Bright Side of Life!” – Higher Hypomania Scores Are Associated with Higher Mental Toughness, Increased Physical Activity, and Lower Symptoms of Depression and Lower Sleep Complaints - Jahangard, Leila; Rahmani, Anahita; Haghighi, Mohammad; Ahmadpanah, Mohammad; Sadeghi Bahmani, Dena; Soltanian, Ali R.; Shirzadi, Shahriar; Bajoghli, Hafez; Gerber, Markus; Holsboer-Trachsler, Edith; Brand, Serge (Frontiers in Psychology, 2017)
Background: In the present study, we explored the associations between hypomania, symptoms of depression, sleep complaints, physical activity and mental toughness. The latter construct has gained interest for its association with a broad variety of favorable behavior in both clinical and non-clinical samples. Subjects and methods: The non-clinical sample consisted of 206 young adults (M=21.3 years; age range: 18-24 years; 57.3% males). They completed questionnaires covering hypomania, mental toughness, symptoms of depression, physical activity, and sleep quality. Results: Higher hypomania scores were associated with higher mental toughness, increased physical activity, lower symptoms of depression and lower sleep complaints. No gender differences were observed. Higher hypomania scores were predicted by higher scores of mental toughness subscales of control, and challenge, and physical activity. Conclusions: The pattern of results suggests that among a non-clinical sample of young adults, self-rated hypomania scores were associated with higher scores on mental toughness and physical activity, along with lower depression and sleep complaints. The pattern of results further suggests that hypomania traits are associated with a broad range of favorable psychological, behavioral and sleep-related traits, at least among a non-clinical sample of young adults.